Umbilical-Cord-Derived Mesenchymal Stromal Cells Modulate 26 Out of 41 T Cell Subsets from Systemic Sclerosis Patients - Paula Laranjeira; Francisco dos Santos; Maria João Salvador; Irina N. Simões; Carla M. P. Cardoso; Bárbara M. Silva; Helena Henriques-Antunes; Luísa Corte-Real; Sofia Couceiro; Filipa Monteiro; Carolina Santos; Tânia Santiago; et al. (Biomedicines, 2023)
Systemic sclerosis (SSc) is an immune-mediated disease wherein T cells are particularly implicated, presenting a poor prognosis and limited therapeutic options. Thus, mesenchymal-stem/stromal-cell (MSC)-based therapies can be of great benefit to SSc patients given their immunomodulatory, anti-fibrotic, and pro-angiogenic potential, which is associated with low toxicity. In this study, peripheral blood mononuclear cells from healthy individuals (HC, n = 6) and SSc patients (n = 9) were co-cultured with MSCs in order to assess how MSCs affected the activation and polarization of 58 different T cell subsets, including Th1, Th17, and Treg. It was found that MSCs downregulated the activation of 26 out of the 41 T cell subsets identified within CD4+, CD8+, CD4+CD8+, CD4−CD8−, and γδ T cells in SSc patients (HC: 29/42) and affected the polarization of 13 out of 58 T cell subsets in SSc patients (HC: 22/64). Interestingly, SSc patients displayed some T cell subsets with an increased activation status and MSCs were able to downregulate all of them. This study provides a wide-ranging perspective of how MSCs affect T cells, including minor subsets. The ability to inhibit the activation and modulate the polarization of several T cell subsets, including those implicated in SSc’s pathogenesis, further supports the potential of MSC-based therapies to regulate T cells in a disease whose onset/development may be due to immune system’s malfunction.